Foto Bonaudi - Chapter 3 - Tarrio, Gustavo (Conjuro, 2006)
Verzio FF Submission The third episode of a documentary series that tells the story of a family of photographers from Santa Fe, New Mexico. This episode looks at the work of Christian Bonaudi, the only member of the Bonaudi family who works in the studio and keeps its distinctive activity alive: portraits.